Causal relationships between serum matrix metalloproteinases and estrogen receptor-negative breast cancer: a bidirectional mendelian randomization study - Zijun Zhao; Qing Cao; Ming Zhu; Chaonan Wang; Xin Lu (Scientific Reports, 2023)
Abstract To better clarify the causal effects between matrix metalloproteinases (MMPs) and estrogen-receptor (ER)-negative breast cancer (BC), we investigated the bidirectional causal relationship between MMPs and ER-negative BC by mendelian randomization (MR) analysis. Summary statistic data of five MMPs were extracted from European participants in 13 cohorts. Data of ER-negative BC collected from one of genome-wide association studies of European ancestry was used as experimental datasets and another four ER-negative BC datasets were used as validation sets. Inverse variance weighted method was used for main MR analysis and sensitivity analysis was also conducted. Serum level of MMP-1 has negative effect on ER-negative BC (odds ratio = 0.92, P = 0.0008) but the latter one was not the cause of the former one, which was supported by validation sets. No bidirectional causal effect was detected between the other four types of MMPs and ER-negative BC (P > 0.05). Sensitivity analysis indicated robustness of the above results without remarkable bias. To conclude, serum MMP-1 may be a protective factor against ER-negative BC. No reciprocal causality was found between the other kinds of MMPs and ER-negative BC. MMP-1 was indicated as a biomarker for risk of ER-negative BC.